(3GdfXQjI GdYGeI aj eGdjI GdOhdIs - (3eMeO(B, (3OhjOGQs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s)
(3COhGJ GdSjGSI GdeGdjI(B- (3fXQjI GdCfaGb GdYGe(B- (3fXQjI GdEjQGO GdYGe(B- (3aj ejRGfjI GdOhdI(B- (3ecGf JjGQGJ GdeGdjI GdYGeI ef JjGQGJ GdONd Gdbhej(B- (3GdSjGSI GdeGdjI aj GdEbJUGO GdQCSeGdj GdeJbOe(B- (3CSGSjGJ GdeGdjI hGdEbJUGO GdeJNdas
Keywords: (3GdEbJUGO GdSjGSjs; (3GdEbJUGO GdeGdjs